2015
DOI: 10.1371/journal.pone.0138757
|View full text |Cite
|
Sign up to set email alerts
|

Vicariance and Its Impact on the Molecular Ecology of a Chinese Ranid Frog Species-Complex (Odorrana schmackeri, Ranidae)

Abstract: Paleogeological events and Pleistocene climatic fluctuations have had profound influences on the genetic patterns and phylogeographic structure of species in southern China. In this study, we investigated the population genetic structure and Phylogeography of the Odorrana schmackeri species complex, mountain stream-dwelling odorous frogs, endemic to southern China. We obtained mitochondrial sequences (1,151bp) of the complete ND2 gene and two flanking tRNAs of 511 individuals from 25 sites for phylogeographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 82 publications
2
28
0
Order By: Relevance
“…1 ). Also, Zhu (2016) based on 12S rRNA and 16S rRNA genes showed a broadly similar phylogeographic framework through a more comprehensive sampling with 78 populations, and supplied several different implications: Clade D in Li et al (2015) should not be recognized as a cryptic species but still be classified as O. schmackeri , and thus O. schmackeri sensu stricto was in fact distributed in western Henan, southeastern Shanan’xi, eastern to central Chongqing, northwestern and eastern Hubei, northwestern Hunan, northeastern Guizhou and Jiangxi provinces in China; O. hejiangensis occupied a large range around Sichuan Basin even in western Henan and eastern Shananxi provinces; one cryptic species ( Odorrana sp1 defined by them) had a large range across central Guizhou and Guangxi provinces; and another cryptic species ( Odorrana sp2 defined by them) occupied a large range around the southern part of Sichuan Basin ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…1 ). Also, Zhu (2016) based on 12S rRNA and 16S rRNA genes showed a broadly similar phylogeographic framework through a more comprehensive sampling with 78 populations, and supplied several different implications: Clade D in Li et al (2015) should not be recognized as a cryptic species but still be classified as O. schmackeri , and thus O. schmackeri sensu stricto was in fact distributed in western Henan, southeastern Shanan’xi, eastern to central Chongqing, northwestern and eastern Hubei, northwestern Hunan, northeastern Guizhou and Jiangxi provinces in China; O. hejiangensis occupied a large range around Sichuan Basin even in western Henan and eastern Shananxi provinces; one cryptic species ( Odorrana sp1 defined by them) had a large range across central Guizhou and Guangxi provinces; and another cryptic species ( Odorrana sp2 defined by them) occupied a large range around the southern part of Sichuan Basin ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 97%
“…However, phylogenetic analyses of Chen et al (2013) indicated that above four species did not form a monophyly, but were nested with some other Odorrana species including two cryptic species, and also strongly rejected the alliance of O. anlungensis , O. yizhangensis , and O. lungshengensis with the O. schmacheri group that was defined based on morphological data ( Fei et al, 2009 ). Therefore, the “ O. schmackeri species complex” was defined referring to the species resembling O. schmackeri on morphology, such as O. nanjiangensis , O. huanggangensis , O. hejiangensis , O. tianmuii , and several cryptic species ( Li et al, 2015 ; Zhu, 2016 ; He, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there was a significant positive correlation between genetic differentiation ( F st ) and geographic distance fit the IBD model in accordance with other studies (Meng et al, ; Pettersen et al, ; Yu et al, ), suggesting that the distribution of genetic variation is due to geographical separation, rather than natural selection. The population genetic differentiation within F. taihangnica and Odorrana schmackeri rejected the IBD model (Li et al, , ; Wang et al, ), indicating high gene flow and panmixia in these species. The remarkable spatial genetic differentiations among F. taihangnica lineages likely reflect the effects of historical isolations induced by tectonic changes and Pleistocene climatic changes (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, phylogeographic information is an effective tool to help define cryptic species (Rissler and Apodaca 2007). Phylogeographic researchers targeting various animals have clearly demonstrated the presence of cryptic species; e.g., the monogonont rotifer, Synchaeta pectinate Ehrenberg 1832 (Kimpel et al 2015); the snail, Semisulcospira libertine Gould, 1859 (Hsu et al 2014); the sow bug, Asellus aquaticus Linnaeus 1758 (Sworobowicz et al 2015); and the frog, Rana schmackeri Boettger 1892 (Li et al 2015). The phylogeographic study of Isonychia japonica Ulmer, 1919 by Saito and Tojo (2016a) and by Saito et al (2016), revealed that I. japonica collected from the Japanese Archipelago is segregated environmentally, with specimens constituting 1 lineage occurring in small-scale rivers of upstream regions and specimens constituting another lineage occurring in large-scale rivers of downstream regions.…”
Section: Volume 37mentioning
confidence: 99%